Molecular detection and phylogenetic identification of Toxoplasma gondii-like strains, Hepatozoon ixoxo and Lankesterella sp. in frogs and toads - Salim, Mubashra; Khan, Asmat Ullah; Niazi, Alaudin Khan; Aqdas, Amna; Dawoud, Turki M.; Usman, Muhammad; Muqaddas, Hira; Ullah, Shakir; Belkahia, Hanène; Khan, Adil; Ben Said, Mourad; Iqbal, Furhan (Frontiers in Veterinary Science, 2025)
IntroductionDespite Pakistan’s rich amphibian fauna, frog and toad species remain largely unexplored regarding blood-borne parasites.MethodsThis study aims to investigate potential infections by toxoplasma gondii and Hepatozoon spp. in four amphibian species (n = 223) collected from various regions in Punjab and Khyber Pakhtunkhwa provinces.ResultsMolecular analyses revealed that 17 out of 223 amphibians (7.6%) were infected with Hepatozoon spp., with the highest infection rates found in Bufo olivaceous (20.0%), followed by Bufo stomaticus (9.3%) and Hoplobatrachus tigerinus (5.05%). DNA sequencing and BLAST analysis confirmed the presence of Hepatozoon ixoxo and Lankesterella sp. phylogenetic analysis of both pathogens demonstrated genetic diversity among the Pakistani isolates, clustering with isolates from birds, amphibians, and reptiles worldwide. To the best of our knowledge, this is first ever report globally where we are documenting that 4.5% of the screened Pakistani anurans, including frogs (H. tigerinus, 8.1%) and toads (B. stomaticus, 1.9%), were infected with toxoplasma gondii-like strains. Parasite prevalence varied between sampling sites and amphibian species. This study represents the first report from Pakistan documenting the prevalence and genetic characterization of Hepatozoon sp., Lankesterella sp., and T. Gondii-like strains among amphibians. We recommend conducting similar large-scale studies across various geo-climatic regions of Pakistan to further explore the epidemiology, genetic diversity, host–parasite interactions, and effective control of these pathogens among local frog and toad species. Identifying genetically related T. Gondii strains in unexpected host animals, such as amphibians, has been crucial for contributing to the elucidation of the parasite’s evolutionary history.